RETRACTED ARTICLE: Fabrication of a magnetic alginate-silk fibroin hydrogel, containing halloysite nanotubes as a novel nanocomposite for biological and hyperthermia applications - Reza Eivazzadeh-Keihan; Zahra Sadat; Hooman Aghamirza Moghim Aliabadi; Fatemeh Ganjali; Amir Kashtiaray; Milad Salimi Bani; Samira Komijani; Mohammad Mahdi Ahadian; Nabi salehpour; Reza Ahangari Cohan; Ali Maleki (Scientific Reports)
Abstract In this study, the main focus was on designing and synthesizing a novel magnetic nanobiocomposite and its application in hyperthermia cancer treatment. Regarding this aim, sodium alginate (SA) hydrogel with CaCl2 cross-linker formed and modified by silk fibroin (SF) natural polymer and halloysite nanotubes (HNTs), followed by in situ Fe3O4 magnetic nanoparticles preparation. No important differences were detected in red blood cells (RBCs) hemolysis, confirming the high blood compatibility of the treated erythrocytes with this nanobiocomposite. Moreover, the synthesized SA hydrogel/SF/HNTs/Fe3O4 nanobiocomposite does not demonstrate toxicity toward HEK293T normal cell line after 48 and 72 h. The anticancer property of SA hydrogel/SF/HNTs/Fe3O4 nanobiocomposites against breast cancer cell lines was corroborated. The magnetic saturation of the mentioned magnetic nanobiocomposite was 15.96 emu g−1. The specific absorption rate (SAR) was measured to be 22.3 W g−1 by applying an alternating magnetic field (AMF). This novel nanobiocomposite could perform efficiently in the magnetic fluid hyperthermia process, according to the obtained results.